Mekanisme Pencegahan Progresivitas Kerusakan Otak Melalui Transplantasi Intraserebral Adipose Derived Neural Stem Cell Pada Iskemia Otak (Analisis TNF-α, IL-10, Ngf, Mda, Caspase-3 Dan Neuron Yang Mengalami Apoptosis Pada Hipokampus Tikus Wistar) - Prastiya Indra Gunawan (2020)
Introduction Until now there has been no neuroprotective therapy that has proven to be effective in improving brain hypoxic ischemia (HI) and apoptosis. Stem cell therapy has the potential role to repair neurological damage caused by HI. Adipose cells are a widely available source of stem cells, without invasive action. The mechanism of Adiposederived Neural Stem Cell (ADNSC) on HI is not yet explained Objective This study aimed to investigate the role of intracerebrally tranplanted ADNSC in prevention of brain damage progressivity in brain ischemia. Methods A post test only control group design was used in 20 weeks-old male Wistar rats that randomized into control, ligation of carotid communis artery (CCA) and treatment (Ligation of CCA and ADNSC intracerebral transplantation) groups. Brain ischemia was induced by ligation of CCA for 2 hours and hypoxia procedure for 60 minute. ADNSC was intracerebrally tranplantated after hypoxia procedure to the treatment group. After 48 hours all rats were sacrified and their brain were immunohistochemically analyzed for expression of IL-10, NGF, MDA, Caspase-3 and TUNEL assay procedure for apoptotic neuron. ANOVA and Kruskal Wallis test were used for statistical analysis. Results There were 24 rats divided into 8 groups each, participating in the study. There were no decrease in TNF-α expression (P <0.05) an increase in IL-10 expression (P <0.05), an increase in NGF expression (P <0.05), a decrease in MDA exppression (P<0.05), a decrease in Caspase-3 expression (P <0.05) and a decrease in the number of apoptotic neurons (P <0.05) in brain ischemia induced CCA ligation after ADNSC transplant intracerebrally. Path analysis showed ADNSC decreased apoptotic neuron through Caspase-3 pathway. Conclusion Prevention of the progression of brain damage in brain ischemia by administering ADNSC intracerebraly can reduce MDA expression and apoptotic neurons through Caspase-3 pathway.